The use and efficacy of question type and an attentive interviewing style in adult rape interviews - Webster, William S. (Psychology, crime & law, 2021)
Police interviewers find the investigation of sexual crimes ‘technically difficult’ and ‘stressful’ to conduct by having to make sense of very powerful and painful emotions. In addition, such interviews often contain inappropriate as opposed to appropriate questions and interviewers often find it difficult to be ‘attentive’ to the specific needs of victims. Through the analysis of interviews with adult rape victims (N = 25) in England, we wanted to establish whether the ‘quantity’ and ‘quality’ of investigation relevant information (IRI) obtained would be impacted as a function of different question typologies (e.g. appropriate versus inappropriate), and overall interviewer attentiveness. We hypothesised that: (i) more inappropriate questions would be asked compared to appropriate questions; (ii) responses to appropriate questions would contain more items of IRI than responses to inappropriate questions; (iii) attentive interviews would contain more appropriate questions than non-attentive interviews, and; (iv) attentive interviews would contain more IRI than non-attentive interviews. Results found that interviewers asked significantly more appropriate questions that elicited significantly more items of IRI. However, there were no significant differences in the number of appropriate questions asked or the impact on the amount of IRI obtained between interviews as a function of interviewer attentiveness. Implications for practice are discussed.